Zwischen Widerstand und Selbstaufopferung. Die rabbinische Rezeption der Gestalt der Hanna (Babylonischer Talmud, Berachot 31a-32b) (lectio difficilior, 2006)
Hannah is one of the powerful women of the Hebrew Bible, but how is she described in rabbinical literature? Based on the text bBer 31a-32b this article deals with the literary construction of a female hero in the Babylonian Talmud. It focuses on the question which “female” qualities the rabbinical authors thought inextinguishable, despite Hannah’s pugnacious character, her fighting against the authorities and power never to give in. [1]